Three-dimensional in vivo imaging of the murine liver: a micro-computed tomography-based anatomical study - Fiebig, Anna Teresa; Boll, Hanne; Negrão de Figueiredo Miller, Giovanna; Kerl, Hans Ulrich; Nittka, Stefanie; Groden, Christoph; Brockmann, Marc Alexander (PLOS ONE, 2012)
Various murine models are currently used to study acute and chronic pathological processes of the liver, and the efficacy of novel therapeutic regimens. The increasing availability of high-resolution small animal imaging modalities presents researchers with the opportunity to precisely identify and describe pathological processes of the liver. To meet the demands, the objective of this study was to provide a three-dimensional illustration of the macroscopic anatomical location of the murine liver lobes and hepatic vessels using small animal imaging modalities. We analysed micro-CT images of the murine liver by integrating additional information from the published literature to develop comprehensive illustrations of the macroscopic anatomical features of the murine liver and hepatic vasculature. As a result, we provide updated three-dimensional illustrations of the macroscopic anatomy of the murine liver and hepatic vessels using micro-CT. The information presented here provides researchers working in the field of experimental liver disease with a comprehensive, easily accessable overview of the macroscopic anatomy of the murine liver.
Gesehen am 12.07.2018